The world watch reader on global environmental issues - Brown, Lester R. (New York : Norton, 1991)
The book examines the activities of the World Watch Institute in ensuring the sustainability of global economy through its vision of environmental sustainability.
Includes index.
usc 22/01/2019
Loans
Keywords: Environmental protection; Pollution; Global environmental change; Economic development